Longitudinal trends in dementia prevalence among individuals with type 2 diabetes in Taiwan (2009–2022) - Chen‐Yang Hsiao; Sun‐Wung Hsieh; Yuan‐Han Yang; Hui‐Min Hsieh (Journal of Diabetes Investigation)
ABSTRACT Objective This study examined the population‐based epidemiological prevalence of early‐ and late‐onset dementia in individuals with type 2 diabetes mellitus (T2DM) compared with the general population in Taiwan from 2009 to 2022. Methods A 14‐year nationwide population‐based epidemiology study from 2009 to 2022 in Taiwan using the Taiwan National Health Insurance Research Database was conducted to examine the crude and age‐standardized dementia prevalence in individuals aged <65 and ≥65. Multivariable logistic regression was used to assess factors associated with dementia prevalence in the T2DM population. Results Among individuals aged ≥65 with T2DM, age‐standardized dementia prevalence increased from 5.83 per 100 in 2009 to 7.11 per 100 in 2022, while the crude prevalence ratio compared to the general population ranged from 1.19 to 1.08. In the 40–64 age group, standardized dementia prevalence ranged from 0.58 to 0.43 per 100, with crude ratios ranging from 1.76 to 1.41. Our study found a higher risk of dementia prevalence among individuals aged 65 years and older, particularly among those with T2DM. Although the overall prevalence of dementia in the 40–64 age group was lower compared to older adults, individuals in this younger group with T2DM exhibited a significantly higher risk of developing dementia. Given these findings, public policy should prioritize early preventive strategies for individuals with T2DM to monitor and mitigate dementia progression in patients with T2DM.